2002
DOI: 10.1038/sj.leu.2402605
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and significance of cryptic chromosome aberrations detected by fluorescence in situ hybridization in acute myeloid leukemia with normal karyotype

Abstract: To better define the incidence and significance of cryptic chromosome lesions in acute myeloid leukemia (AML), fluorescence in situ hybridization (FISH) studies were performed in interphase cells and, when appropriate, in metaphase cells and in morphologically intact BM smears. Fifty-five adult de novo AML (group A) and 27 elderly AML or AML after myelodysplastic syndrome (AML-MDS) (group B) were tested using probes detecting the following anomalies: −5, −7, +8, deletions of 5q31, 7q31, 12p13/ETV6, 17p13/p53, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 33 publications
1
24
1
1
Order By: Relevance
“…Our data are also in line with a recent study, which suggested that the loss of chromosome material is a pathogenetic mechanism operative in a fraction of MDS/AML carrying an apparently normal karyotype. 26 In our series, a FISH minor aneuploid cell population (18-25% cells) was identified on clinical diagnosis in three patients (one each with þ 11, À7 and þ 8), who presented at least one monosomic or trisomic cell on metaphase FISH. This datum suggests that CC failed to reveal the chromosome defect not because of its low sensitivity, but rather because of the inability of the dysplastic clone to divide properly in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our data are also in line with a recent study, which suggested that the loss of chromosome material is a pathogenetic mechanism operative in a fraction of MDS/AML carrying an apparently normal karyotype. 26 In our series, a FISH minor aneuploid cell population (18-25% cells) was identified on clinical diagnosis in three patients (one each with þ 11, À7 and þ 8), who presented at least one monosomic or trisomic cell on metaphase FISH. This datum suggests that CC failed to reveal the chromosome defect not because of its low sensitivity, but rather because of the inability of the dysplastic clone to divide properly in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…29,39,40 In contrast, other studies have pointed out that FISH identifies minor clonal cell populations marked by À7 or by other structural defects in a significant number of CC normal patients. [22][23][24][25][26]33 Two recent reports, which revealed occult karyotype abnormalities in 17.8 and 29.6% of patients, have further stressed the crucial role of interphase/metaphase FISH in the definition of chromosomally normal MDS/AML. 25,26 In the present study, which includes more RAEB and RAEB-t patients (49 vs 40%) than that of Rigolin et al, 25 the incidence of occult defects was 15%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations